GURU LAKI-LAKI PADA PENDIDIKAN ANAK USIA DINI - Widayati, Widayati (Jurnal Pendidikan Usia Dini, 2016)
This research was determinate to describe about male teacher in early childhoodeducation. This research was do in the TK Bahrul Maghfiroh Malang. This research is qualitativeresearch with case study methode. Data analysis used Miles and Hubberman. Research data fromobservation, interview and documentasion. The result of this research show up about:1)Theimpact of male teachers for early childhood education, 2) Bahrul Maghfiroh institutions giveconsideration role of male teachers, 3) The process of learning the role of male teachers, 4)Publicperceptions of male teachers. The role of male teachers have an impact on children's dress,emotional resilience, children's early understanding ofgender roles, the formation ofplay groupsand play groups election. Bahrul Maghfiroh foundation as a boarding school is a majorconsideration institute son his role in male teachers. Curriculum implemented in kindergartensBahrul Maghfiroh refers curriculum education office. learners are dominated by men. Learningmethods are used storytelling, assignment method, field trips and debriefing. Utilizinginstructional media used items available in schools. Approach to the children of male teachersneed a figure of female teachers. Public perception of the role of male teachers who teach inkindergarten is still negative.